2022
DOI: 10.1161/circresaha.121.320625
|View full text |Cite|
|
Sign up to set email alerts
|

A Single Nucleotide Polymorphism in SH2B3/LNK Promotes Hypertension Development and Renal Damage

Abstract: Rationale: SH2B3 (SH2B adaptor protein 3) is an adaptor protein that negatively regulates cytokine signaling and cell proliferation. A common missense single-nucleotide polymorphism in SH2B3 (rs3184504) results in substitution of tryptophan for arginine at amino acid 262 and is a top association signal for hypertension in human genome-wide association studies. Whether this variant is causal for hypertension, and if so, the mechanism by which it impacts pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 89 publications
0
15
1
Order By: Relevance
“…These findings suggest that the rs3184504 minor allele is a causal variant for hypertension through at least a partial loss of function of Sh2b3 resulting in enhanced T-cell IFNg production. 40 Although Mori et al demonstrated that Sh2b3 deficiency can have cell intrinsic effects in both DCs and T cells to promote IFNg production, 41 we did not find significant differences in dendritic and other myeloid cell cytokine production in mice with the Sh2b3 minor versus major alleles. 40 Hence, it seems that Sh2b3 plays a particularly key role in limiting T-cell activation and cytokine production in hypertension.…”
Section: Sh2b3/lnkcontrasting
confidence: 66%
See 2 more Smart Citations
“…These findings suggest that the rs3184504 minor allele is a causal variant for hypertension through at least a partial loss of function of Sh2b3 resulting in enhanced T-cell IFNg production. 40 Although Mori et al demonstrated that Sh2b3 deficiency can have cell intrinsic effects in both DCs and T cells to promote IFNg production, 41 we did not find significant differences in dendritic and other myeloid cell cytokine production in mice with the Sh2b3 minor versus major alleles. 40 Hence, it seems that Sh2b3 plays a particularly key role in limiting T-cell activation and cytokine production in hypertension.…”
Section: Sh2b3/lnkcontrasting
confidence: 66%
“…Alternative approaches include inhibiting Jak-Stat signaling to limit T-cell activation, particularly Stat4, which promotes enhanced IFNg expression and is activated to a greater degree in T cells harboring the SH2B3 minor allele. 42 This approach may be particularly efficacious in those of European ancestry who have a minor allele frequency for this variant of . 40%.…”
Section: Sh2b3/lnkmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting the immune system to lower blood pressure and reduce organ damage has proven complicated ( 201 , 202 ), but organ specific immune targeting using nanotechnology appears to be a promising solution to reduce toxicities ( 155 , 199 ). Recent identification of single nucleotide polymorphisms in SH2B adaptor protein 3 contributing to T cell involvement in hypertension and renal damage ( 203 ) further complicates therapeutic targeting as genetic mutations may predispose certain immune cells to promote inflammation, supporting consideration of individual patient genetic predispositions when identifying driving factors of hypertension to design future treatment plans, as is becoming increasingly debated ( 204 ). As contributing immune players and inflammation-mediating molecules are characterized, novel pathways can be identified and targeted therapeutically to lower blood pressure and attenuate hypertension-mediated organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Additional prudence, then, is warranted when discussing IFNγ-related mechanisms. Several recent preclinical studies have continued to uncover the molecular mechanisms by which IFNγ mediates the progression of cardiovascular diseases [ 6 ▪ , 24 ▪ , 29 ▪▪ , 30 ▪▪ , 31 ▪ , 32 ▪ ], and several recent clinical studies corroborate, at minimum, a correlation between IFNγ and elevated systolic blood pressure [ 33 ▪ , 34 ▪▪ , 35 ▪ ]. This review will highlight these recent findings from the last two years and discuss them in the context of presently understood mechanisms.…”
Section: Introductionmentioning
confidence: 99%